Molecular diagnosis of peste des petits ruminants virus (PPR) in goats and sheep populations - Abdel-Rady, A (Journal of the Hellenic Veterinary Medical Society, 2022)
Peste des petits ruminants (PPR) is an economically important viral disease of goats and sheep. The disease is confused clinically with other infections such as the mild strain of rinderpest in small ruminants. Effective control measures for PPR need that a proper and rapid diagnostic technique of disease. Therefore, the use of reverse transcriptase-polymerase chain reaction (RT-PCR) to detect suspected field samples collected from diseased goats and sheep in Dammam city, Kingdom of Saudia Arabia (KSA) has helped to give an effective diagnosis that was needed to control measure of the spread of the disease. This assay is based on the rapid purification of RNA on glass beads followed by the reverse transcription-polymerase chain reaction (RT-PCR). The primers (NP3/NP4) were used to amplify specifically a fragment of about 350 bp, that technique has a more specific and sensitive method for rapid diagnosis of disease. Key words: Peste des petits ruminants virus; reverse transcriptase polymerase chain reaction; diagnosis; goats; sheep